Learning to be Researchers: A Study of Pedagogical Students in Hanoi, Vietnam - Nguyen Thi Thu Thao; Nguyen Duy Anh; Nguyen Ngoc To Ngan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2017)
Doing research in colleges and universities is an essential activity since it may provide students a good basis to become professional researcher and teacher in the future. However, few students in Vietnam can recognize the importance of research activities or possess an adequate background of knowledge to participate in these activities, and additionally, the obligatory course of Research Methodology offered in many universities cannot bring enough understanding in doing research to students. This study, thus, aims at investigating the effects of Research Methodology courses in both of their good and bad sides) on students at a pedagogical university. The study also attempts to survey the attitude of those students toward the activity of doing research and the impact of the attitude on their process of learning to be researchers